Untargeted metabolomics screening reveals unique secondary metabolite production from Alternaria section Alternaria - Witte, Thomas E.; Villenueve, Nicolas; Shields, Samuel W.; Sproule, Amanda; Eggertson, Quinn; Kim, Natalie E.; Boddy, Christopher N.; Dettman, Jeremy R.; Overy, David P. (Frontiers in Molecular Biosciences, 2022)
Alternaria section Alternaria is comprised of many species that infect a broad diversity of important crop plants and cause post-harvest spoilage. Alternaria section Alternaria species, such as A. alternata and A. arborescens, are prolific producers of secondary metabolites that act as virulence factors of disease and are mycotoxins that accumulate in infected tissues – metabolites that can vary in their spectrum of production between individuals from the same fungal species. Untargeted metabolomics profiling of secondary metabolite production using mass spectrometry is an effective means to detect phenotypic anomalies in secondary metabolism within a species. Secondary metabolite phenotypes from 36 Alternaria section Alternaria isolates were constructed to observe frequency of production patterns. A clear and unique mass feature pattern was observed for three of the strains that were linked with the production of the dehydrocurvularin family of toxins and associated detoxification products. Examination of corresponding genomes revealed the presence of the dehydrocurvularin biosynthesis gene cluster associated with a sub-telomeric accessory region. A comparison of sequence similarity and occurrences of the dehydrocurvularin biosynthetic gene cluster within Pleosporalean fungi is presented and discussed.